Marginalization as a Site of Resistance: Women’s Subversive Power in Akiyoshi Rikako's Works - Risman, Yunita El (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study explore of Marginalization as a Site of Resistance in Akiyoshi Rikako’s works, particularly 暗黒女子(Ankoku Joshi), 聖母(Seibo), and絶対正義(Zettai Seigi). These novels depict marginalized women in a patriarchal societies who leverage their positions to resist the patriarchy structures. This study employs a qualitative approach, integrating Norman Fairclough’s Critical Discourse Analysis (CDA) and bell hooks’ feminist theory. The findings reveal three primary forms of resistance: (1) resistance to gender discrimination; (2) resistance to gender based violence; and (3) resistance against the double burden. Akiyoshi Rikako’s works illustrate how female marginalization can function both as a mechanism of patriarchal structures and as catalyst for empowerment, allowing women to harness their subversive potential. By framing marginalization as a transformative space, this study contributes to broader discussions on gender justice and dismantling of patriarchal systems. The social implications suggest that recognizing marginalization as a site of resistance can inspire real-world activism, empowering marginalized groups, particularly women, to turn their social positions into sources of strength and agency. This study underscores how marginalization can create spaces for resistance and dismantling patriarchal structures that control women’s lives.Keywords: Akiyoshi Rikako, Marginalization, Resistance, Subversive Power, bell hooks